The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3906/vet-1907-81
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium and zinc supplementation on cadmium toxicity in broilers

Abstract: Materials and methods Animals, diets, and experimental designOne hundred eighty, as-hatched, 1-day-old, Cobb 500, chickens (broilers) were used in total. Broiler chickens were purchased from a commercial hatchery. There were 4 replicate pens (2 m length × 1 m width) of 3 dietary treatments namely T1, T2, and T3, randomly allocated in the house. Pen was the experimental unit. There were 15 chickens per pen, 60 per treatment. In T1 treatment, Se, Cd, and Zn were added to a basal broiler diet (only naturally pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The physiological role of Se in the body relates to activity of glutathionperoxidase (GSH-Px). Se is incorporated in the active site of this enzyme which acts as a free radical scavenger in the body protecting cellular membranes against oxidative stress products (Zoidis et al, 2020). The data of Table 2 showed that intake of diet supplemented with Se prevented Cd-induced disturbance of antioxidant-prooxidant balance in chickens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological role of Se in the body relates to activity of glutathionperoxidase (GSH-Px). Se is incorporated in the active site of this enzyme which acts as a free radical scavenger in the body protecting cellular membranes against oxidative stress products (Zoidis et al, 2020). The data of Table 2 showed that intake of diet supplemented with Se prevented Cd-induced disturbance of antioxidant-prooxidant balance in chickens.…”
Section: Resultsmentioning
confidence: 99%
“…Natural antioxidants including minerals and vitamins play a vital role in the maintenance of antioxidant status in biological systems (Surai, 2019). The protective effect of dietary zinc (Zn) and selenium (Se) against Cd toxicity was studied in broilers (Zoidis et al, 2020). Zn is one of the most important essential trace elements and forms an integral component of several cellular enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Natural antioxidants including minerals and vitamins play a vital role in the maintenance of antioxidant status in biological systems (Surai, 2019). The protective effect of dietary zinc (Zn) and selenium (Se) against Cd toxicity was studied in broilers (Zoidis et al, 2020). Zn is one of the most important essential trace elements and forms an integral component of several cellular enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Since it is impossible to eliminate Pb and Cd from food, research is carried out on methods of limiting its absorption by the body. These methods should be easily accessible and uncomplicated [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Foods containing significant amounts of antioxidant components can be used in the daily diet to prevent the dangerous effects of toxic metals on the human body [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%